2012
DOI: 10.1017/s1355617711001925
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Fluency in Patients Receiving Bilateral versus Left-Sided Deep Brain Stimulation of the Subthalamic Nucleus for Parkinson's Disease

Abstract: The purpose of this study was to investigate the relative effects of unilateral (left-sided) versus bilateral deep brain stimulation (DBS) of the subthalamic nucleus (STN) on verbal fluency. To do this, 10 Parkinson's disease patients with predominantly bilateral motor symptoms who received bilateral STN DBS were compared with 6 patients suffering from predominantly unilateral symptoms who received STN DBS on the left side only. The results suggest that unilateral STN DBS of the speech dominant hemisphere is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
17
1
Order By: Relevance
“…In contrast to our results, a recent study showed more decline in verbal fluency in patients who received bilateral stimulation compared with only left-side stimulation, questioning the role of right STN in verbal fluency [34] .…”
Section: Verbal Fluencycontrasting
confidence: 99%
“…In contrast to our results, a recent study showed more decline in verbal fluency in patients who received bilateral stimulation compared with only left-side stimulation, questioning the role of right STN in verbal fluency [34] .…”
Section: Verbal Fluencycontrasting
confidence: 99%
“…[33] and Sjöberg et al . [31] Speech worsening also seems to be influenced by anteroposterior and mediolateral location because we observed more dysarthria for posterior and lateral locations; however, medial and anterior contact positions appear to be equally involved. [3334] This variability could be related to the patient studied and the method of contact location analysis used.…”
Section: Discussionmentioning
confidence: 88%
“…Specifically, there have been differential findings in Parkinson disease with most studies suggesting that neuropsychological performance remains unchanged [15] or improves across time with DBS (applied to the subthalamic nucleus), though one study reported a decrease in phonemic fluency. [16] Decreased verbal fluency secondary to DBS (applied to the anterior limb of the internal capsule) was also reported in a study to treat obsessive compulsive disorder. [17] Interestingly, a recent investigation [18, 19] found that DBS applied to the fornix improved performance in global cognitive function and memory for patients with Alzheimer’s disease.…”
Section: Introductionmentioning
confidence: 87%